Crop production in the USA is frequently limited by a lack of pollinators. Issue 1931 (29th July 2020) - Reilly, J. R.; Artz, D. R.; Biddinger, D.; Bobiwash, K.; Boyle, N. K.; Brittain, C.; Brokaw, J.; Campbell, J. W.; Daniels, J.; Elle, E.; Ellis, J. D.; Fleischer, S. J.; et al.
Abstract : Most of the world's crops depend on pollinators, so declines in both managed and wild bees raise concerns about food security. However, the degree to which insect pollination is actually limiting current crop production is poorly understood, as is the role of wild species (as opposed to managed honeybees) in pollinating crops, particularly in intensive production areas. We established a nationwide study to assess the extent of pollinator limitation in seven crops at 131 locations situated across major crop-producing areas of the USA. We found that five out of seven crops showed evidence of pollinator limitation. Wild bees and honeybees provided comparable amounts of pollination for most crops, even in agriculturally intensive regions. We estimated the nationwide annual production value of wild pollinators to the seven crops we studied at over 1.5 billion; the value of wild bee pollination of all pollinator-dependent crops would be much greater. Our findings show that pollinator declines could translate directly into decreased yields or production for most of the crops studied, and that wild species contribute substantially to pollination of most study crops in major crop-producing regions.